Change and entrenchment in Irish maternity care policies and antenatal practices: An Institutional Ethnography - Dunlea, Margaret (Trinity College Dublin. School of Nursing & Midwifery. Discipline of Nursing, 2022)
Abstract Change and entrenchment in Irish maternity care policies and antenatal practices: An Institutional Ethnography Margaret Dunlea Background The Mother and Infant Care Scheme (MICS) (1954), enacted following the Health Act of 1953, is widely acknowledged as the foundation of the Irish state-run maternity service as we know it today. Its underlying approach was shaped by the conservative, patriarchal society from which it emerged and the powerful obstetric profession. The MICS effectively institutionalised what became a heavily centralised, biomedical model of maternity care that was heavily determined by obstetric-dominated government policy. The entrenchment of the biomedical model for all births has persisted, despite mounting evidence supporting the bio-phychosocial model of care. The consensus is that current Irish maternity services are out of step with international best evidence. Meaningful, whole systems change in the Irish maternity services is urgently needed. Methodology This study is an exploration of change and entrenchment in Irish maternity services policies and practices using an institutional ethnographic approach; this is related to the need to go beyond the local particularities of people working within institutions to the broader ?relations of ruling? that shape those daily realities. The study consists of macro historical analysis of the key tenets of Modernity that underpin the biomedical model and the power-relations embedded in government policy and legislation since the introduction of the MICS in 1954. The study also involved a micro analysis involving observational recordings of the antenatal encounter followed by interviews of service-users and providers as part of the methodology; micro refers to antenatal date generation and macro refers to primary archival documentation. I used a critical institutional ethnography with a feminist perspective, framed by Dorothy Smith, drawing on Foucault?s critique of power/knowledge. This reflects an interpretive ontology and epistemology which assumes that realities are multiple, socially constructed, context-specific and relational. Results The study reveals that the routinized antenatal practices and discourses reflect the wider historical, political, structural and cultural power-relations and social processes. The link between modernity, the capitalism mode of production, state run maternity services, obstetric hegemony, the side-lining of midwives and women?s disempowerment are made. These organizational and institutional processes are not so much overtly political as part of an entrenched power establishment that goes unchallenged and unseen. The power of the biomedical paradigm is its ability to reproduce the social structure and processes that support it, without appearing coercive. Healthcare professionals, through their discourses and practices, knowingly or unknowingly, perpetuate traditional, patriarchal views of power embedded in the biomedical model, thus perpetuating the subjugation of childbearing women and midwives. Medical hegemony was such that Irish obstetrics, not alone remained a ?traditionally? unchallenged site of power from the foundation of the state onwards, but right up through the 1970s and beyond, where obstetrics knowledge and expertise continued to single-handedly drive maternity care policy. This study demonstrates that government policies have still not made the connection between obstetric modernist thinking, the bureaucratic centralised approach, the biomedical model, the technocratic imperative and the current problems in maternity care. This amounts to a gendered politics of knowledge and expertise, where women?s voices continue to be silenced or trivialised. Conclusion Maternity services are complex, multi-layered, interconnected systems. For meaningful change to occur, whole system change that disrupts the current power-relations is required. An in-depth understanding of the biomedical paradigm in obstetrics, in terms of the three imperative: obstetric, risk and technological, and the bureaucratic, institutional structures that perpetuate it are urgently needed if meaningful change is to occur. Unmasking power-relations by exposing how power works in institutions can be emancipatory and makes resistance and change possible. Change processes are not logical and linear but unpredictable, with often unintended consequences. Up to now most changes to the maternity services have been partial, fragmented and local which impedes their integration into the whole system, making them vulnerable to being withdrawn by the ruling elite. Enacting and embodying changes in practice at local level can influence a change of attitude among service-users and providers through change in action. Because the subordination of midwives is historically entrenched and institutionalised, autonomous midwifery practice is always under threat. To safeguard the midwifery profession and thus safeguarding women?s choices and the provision of a quality and safe maternity services, solidarity and concerted campaigning is needed and all midwives need to be politically active.
APPROVED
Keywords: Institutional ethnography, maternity care, Feminism, Foucault, power-relations, models of maternity care, change processes, risk society